Śrīpaulacaritraṃ = A short life of the Apostle Paul, with a summary of Christian doctrine, as unfolded in his epistles (W.H. Haycock, Bishop's College Press, 1850)
On the life and teachings of Paul, the Apostle, Saint; includes translation in English.